Computational modelling of wounded tissue subject to negative pressure wound therapy following trans-femoral amputation - Zeybek, B.; Li, S.; Fernandez, J. W.; Stapley, S.; Silberschmidt, V. V.; Liu, Y. (Biomechanics and modeling in mechanobiology, 2017)
Proof-of-concept computational models were developed and applied as tools to gain insights into biomechanical interactions and variations of oxygen gradients of wounded tissue subject to negative pressure wound therapy (NPWT), following trans-femoral amputation. A macro-scale finite-element model of a lower limb was first developed based on computed tomography data, and distributions of maximum and minimum principal stress values we calculated for a region of interest (ROI). Then, the obtained results were applied iteratively as new sets of boundary conditions for a specific spatial position in a capillary sub-model. Data from coupled capillary stress and mass- diffusion sub-models were transferred to the macro-scale model to map the spatial changes of tissue oxygen gradients in the ROI. The −70 mmHg NPWT resulted in a dramatic change of a wound surface area and the greatest relative contraction was observed at −150 mmHg. Tissue lateral to the depth of the wound cavity revealed homogenous patterns of decrease in oxygenation area and the extent of such decrease was dependent on the distance from the wound surface. However, tissue lateral to the width of the wound demonstrated heterogeneous patterns of change, as evidenced by both gradual increase and decrease in the oxygenation area. The multiscale models developed in the current study showed a significant influence of NPWT on both macro-deformations and changes of tissue oxygenation. The patterns of changes depended on the depth of the tissue, the geometry of the wound, and also the location of tissue plane.